It's your choice - on the design and implementation of a flexible metalevel architecture - CAHILL, VINNY (IEEE Computer Society, 1996)
Traditional configurable operating systems typically provide a fixed and limited set of functionality. We propose a metalevel architecture, where application-defined objects can choose from a rich selection of possible configurations and are therefore able to dynamically change the way in which they are executed to the configuration that suits best. This allows applications to adapt operating system behaviour to even unanticipated requirements during run-time. A distributed application which processes multimedia data serves as an example to illustrate the concepts described.
Proceedings of the 3rd International Conference on Configurable Distributed Systems (ICCDS '96).
3rd International Conference on Configurable Distributed Systems (ICCDS '96).
PUBLISHED
Annapolis, MD, USA
Keywords: configuration management multimedia computing network operating systems software reusability systems analysis